PERENCANAAN DAN PENGENDALIAN VISUAL PRODUKSI PROGRAM KUIS 3 PROGRAM KARTUN IPIN UPIN MENIT DI MNC TV - Tuty Mutiah; Agung Raharjo; Anisti Anisti (Cakrawala - Jurnal Humaniora, 2018)
For planning and controlling visual production programs There are several things that must be considered. One of the most important directors who are required to be creative in the field of cinematography in order to produce good visualizations of scenarios and manuscripts that have previously been made. In addition, the director controls the production he handles and coordinates with elements, facilities and team members in the studio. The research conducted by this author is descriptive with a qualitative approach. The purpose of this research is to make a description and architecture, explain the processes that occur in it, and explain the various contexts behind the event. So qualitative descriptive is a type of research used to make accurate, factual and accurate descriptions, facts or facts about facts, characteristics of descriptions, conditions or phenomena by using data in the form of words or verbally from people and objects used to find or explain relationships, also not to examine facts or make predictions. The director's role in the making and controlling of the visual quiz production program 3 the Ipin Cartoon Program Up in Minutes In MNCTV is not only one part but can also be overcome properly and can work with all concerned.